Effect of montmorillonite nanoclay and sulphur-modified blends on the properties of bituminous mixes - vivek A.; Sukhija M.; Singh K.L. (My University, 2025)
This study compares the performance of asphalt mixtures using montmorillonite (MMT) nanoclay and sulphur as a modifier. The head sight of this study is to characterize the physical and strength characteristics of MMT nanoclay and sulphur-modified asphalt binders. In the experimental testing, MMT nanoclay (2,4,6,8) %, sulphur (2,4,6,8) %, and MMT nanoclay–sulphur composite (2,4,6,8) % by weight of asphalt binder were blended. Thereafter, the influence of selected modifiers on the physical properties, strength characterization, and moisture damage was evaluated. The addition of modifiers decreased the penetration value, whereas there was a considerable increase in the softening point. Among all the modifiers, maximum stability value of 34.17 kN has been reported by adding 4% of MMT nanoclay and sulphur in combined form, i.e., 2% MMT nanoclay and 2% sulphur as a composite (50:50), which is 2.8 times the stability of neat asphalt mix at optimum binder content (OBC). MMT nanoclay–sulphur composite has been the most effective blend in improving moisture susceptibility, as tensile strength ratio (TSR) values were relatively greater than 90%. Overall, the addition of MMT nanoclay, S, MMT nanoclay–sulphur composite would improve the resistance against cracking and reduces the moisture damage potential at all the test conditions. © 2021, Springer Nature Switzerland AG.